Power and Promise of Next-Generation Sequencing in Liquid Biopsies and Cancer Control. (14th August 2020) - Wu, Ting-Miao; Liu, Ji-Bin; Liu, Yu; Shi, Yi; Li, Wen; Wang, Gao-Ren; Ma, Yu-Shui; Fu, Da
Traditional methods of cancer treatment are usually based on the morphological and histological diagnosis of tumors, and they are not optimized according to the specific situation. Precision medicine adjusts the existing treatment regimen based on the patient's genomic information to make it most suitable for patients. Detection of genetic mutations in tumors is the basis of precise cancer medicine. Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize damage to healthy tissues, and optimize resources. In recent years, next-generation sequencing technology has developed rapidly and has become the core technology of precise targeted therapy and immunotherapy for cancer. From early cancer screening to treatment guidance for patients with advanced cancer, liquid biopsy is increasingly used in cancer management. This is as a result of the development of better noninvasive, repeatable, sensitive, and accurate tools used in early screening, diagnosis, evaluation, and monitoring of patients. Cell-free DNA, which is a new noninvasive molecular pathological detection method, often carries tumor-specific gene changes. It plays an important role in optimizing treatment and evaluating the efficacy of different treatment options in clinical trials, and it has broad clinical applications.